2019
DOI: 10.1111/bjh.15878
|View full text |Cite
|
Sign up to set email alerts
|

S100A16suppresses the growth and survival of leukaemia cells and correlates with relapse and relapse free survival in adults with Philadelphia chromosome‐negative B‐cell acute lymphoblastic leukaemia

Abstract: Summary Refinement of risk stratification in Philadelphia chromosome (Ph)‐negative B‐cell acute lymphoblastic leukaemia (ALL) might aid the identification of patients who are likely to relapse. Abnormal S100 calcium binding protein A16 (S100A16) has been implicated in various cancers, but its function remains unclear. We found S100A16 transcript levels were higher in 130 adults with newly‐diagnosed Ph‐negative B‐cell ALL compared with 33 healthy controls. In 115 of 130 patients who achieved first complete remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The definition of overexpression is the basis for analysing the clinical significance of RASD1 in Ph-negative B-ALL. In this study we used the median transcript level of RASD1 in Ph-negative B-ALL patients to divide the patients into a high expression group and a low expression group as reported [20,27]. We found that a low RASD1 transcript level at diagnosis was associated with a higher risk of relapse in patients with Phnegative B-ALL, especially in patients receiving chemotherapy only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The definition of overexpression is the basis for analysing the clinical significance of RASD1 in Ph-negative B-ALL. In this study we used the median transcript level of RASD1 in Ph-negative B-ALL patients to divide the patients into a high expression group and a low expression group as reported [20,27]. We found that a low RASD1 transcript level at diagnosis was associated with a higher risk of relapse in patients with Phnegative B-ALL, especially in patients receiving chemotherapy only.…”
Section: Discussionmentioning
confidence: 99%
“…However, this correlation should be interpreted with caution, because it may be partially due to the relatively small number of cases in the allo-HSCT group. In addition, many factors may affect the outcome of allo-HSCT, such as donor-recipient gender matching, HLA disparity, and monitoring and intervention for MRD [20]. An analysis combining RASD1 transcript levels and the known factors in a large cohort may achieve a better understanding of the prognostic value of RASD1 in B-ALL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All mice were pre-treated with an intraperitoneal (i.p.) injection of CTX at a dose of 100 mg/kg once daily for two consecutive days (24). Mice were then injected intravenously (i.v.)…”
Section: Tumor Xenograft Modelmentioning
confidence: 99%